A high-efficiency denitrification bioreactor for the treatment of acrylonitrile wastewater using waterborne polyurethane immobilized activated sludge. (September 2017) - Dong, Honghong; Wang, Wei; Song, Zhaozheng; Dong, Hao; Wang, Jianfeng; Sun, Shanshan; Zhang, Zhongzhi; Ke, Ming; Zhang, Zhenjia; Wu, Wei-Min; Zhang, Guangqing; Ma, Jie
Graphical abstract: Highlights: The immobilized activated sludge with waterborne polyurethane carrier was used. Immobilized denitrification reactor was tested to treat acrylonitrile wastewater. Optimal conditions include C/NO3 − -N ratio of 2.0 and carrier filling rate of 20%. Total nitrogen removal efficiency reached 98% under optimal conditions. Rhodocyclaceae and Pseudomonadaceae were major bacteria in denitrification process. Abstract: The performance of a laboratory-scale, high-efficiency denitrification bioreactor (15 L) using activated sludge immobilized by waterborne polyurethane in treating acrylonitrile wastewater with high concentration of nitrate nitrogen (249 mg/L) was investigated. The bioreactor was operated at 30 °C for 220 days. Batch denitrification experiments showed that the optimal operation parameters were C/NO3 − -N molar ratio of 2.0 using sodium acetate as electron donor and carrier filling rate of 20% (V/V) in the bioreactor. Stable performance of denitrification was observed with a hydraulic retention time of 30 to 38 h. A volumetric removal rate up to 2.1 kg N/m 3 ·d was achieved with a total nitrogen removal efficiency of 95%. Pyrosequencing results showed that Rhodocyclaceae and Pseudomonadaceae were the dominant bacterial families in the immobilized carrier and bioreactor effluent. The overall microbial diversity declined as denitrifiers gradually dominated and the relative abundance of other bacteria decreased along with testing time.